2001
DOI: 10.1002/jcc.1084
|View full text |Cite
|
Sign up to set email alerts
|

MD‐based CD calculations for the assignment of the absolute axial configuration of the naphthylisoquinoline alkaloid dioncophylline A

Abstract: ABSTRACT:The circular dichroism (CD) of the biaryl alkaloid dioncophylline A (2) was investigated by CD calculations; the structures were generated by molecular dynamics (MD) simulations using the force field CVFF. From these structures the CD spectra were calculated with the semiempirical method CNDO/2S. Summing up the single CD spectra yielded the final spectrum. In contrast to our earlier method based on the Boltzmann weighting, the MD-assisted approach permitted to assign the flexible biaryl axis of dionco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…15 As already shown in the case of the related bisbibenzyl isoplagiochin C, 12 the calculations for isoplagiochin D (1) proved the 'upper' axis (joining C-12 0 and C-14) to be configurationally more stable at room temperature as compared to the 'bottom' one (connecting C-2 0 and C-6). Arbitrarily starting with the M-configured stable biaryl axis of 1, the MD simulation was carried out at a virtual temperature of 1300 K using the TRIPOS force field.…”
Section: Optically Active Bisbibenzylsmentioning
confidence: 73%
“…15 As already shown in the case of the related bisbibenzyl isoplagiochin C, 12 the calculations for isoplagiochin D (1) proved the 'upper' axis (joining C-12 0 and C-14) to be configurationally more stable at room temperature as compared to the 'bottom' one (connecting C-2 0 and C-6). Arbitrarily starting with the M-configured stable biaryl axis of 1, the MD simulation was carried out at a virtual temperature of 1300 K using the TRIPOS force field.…”
Section: Optically Active Bisbibenzylsmentioning
confidence: 73%
“…Semiempirical methods -CNDO/S, [35] INDO/S, [36] MNDO-based (e.g., OM2), [37] and SCF-CI-DV MO [5] approaches -have been widely applied, and many research groups have used them as tools for the determination of the absolute configurations of a great variety of chiral com-pounds, such as vinblastine alkaloids, by Berova et al, [49] bridged biphenyls, by Sandström, [50] or fullerenes, by Diederich et al [51] In 1997, the concept of UV correction for achieving better agreement between the theoretical UV and CD spectra and the experimentally measured ones, introduced by our group, was a further significant improvement. [9] Many configurational assignments followed, relating mainly to rotationally hindered biaryl axes such as in dioncophylline A [52] or murastifoline F, [53] but also to "molecular chiralities" as in isoplagiochins C and D, [54,55] or to twofold alkylidene-bridged biaryls possessing both planarchiral elements and chiral axes. [56] Unfortunately, the determination of the UV shifts is not always a trivial matter when applying semiempirical methods.…”
Section: Semiempirical Methods: Configurational Assignment At the Chimentioning
confidence: 99%
“…2, 4, 6, 8, and 10). [52][53][54][55][56][57][58][59][60][61][62][63][64][65] Exploratory calculations on eremophilane and related lactones indicated that the overall appearance of the simulated CD spectra was dominated by the configuration at C 8 . 66 Inverting the configuration at C 2 , the overall shape and the positions of the maximum and minimum on the wavelength scale of the simulated CD spectrum of compound 8 remained almost unchanged apart from slight differences concerning the amplitude (Fig.…”
Section: Calculated Structural Properties Electronic Excitation Enermentioning
confidence: 99%